Do’s and don’ts in evaluation of endoscopic screening for gastrointestinal cancers - Bretthauer, Michael; Kalager, Mette; Adami, Hans-Olov (Endoscopy, 2016)
Endoscopic screening for cancers of the esophagus, stomach, and colon has been introduced in many countries of the world. Endoscopic screening has the potential to reduce incidence and mortality of the target diseases, but may also be harmful and have unwanted side effects. Precise estimates of the magnitude of benefits and harms of endoscopic screening for cancer are a prerequisite for informed decision making for or against participation in screening for individuals in the target population. This paper outlines the most common pitfalls in the evaluation of screening and offers some recommendations for future studies.